Assessing Brand Switching Patterns of Malaysian Pepper Exports - Jurin Gunsalam; Wong, Hock Tsen (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2023)
This study provides an analysis into the competitive dynamics of pepper exports, focusing on key rival exporting countries: Malaysia, Indonesia, and Vietnam. The research encompasses vital export markets, including China and the USA, employing a structured brand-switching framework to identify shifts in consumer preferences for analogous products and brands. The brand-switching study operates under the assumption of consistent market dimensions throughout the study, where every customer transaction involves exposure to the complete array of evaluated products with a uniform transaction quantity. The forthcoming analysis aims to explore brand competitiveness in specific market contexts, acknowledging the term ‘brand’ to encompass exporting countries, in line with international trade conventions regarding pepper products. The research delves into two distinct forms of pepper products sourced from the Piper genus: neither crushed nor ground pepper (HS090411) and crushed or ground pepper (HS090412). These types wield significant influence in global trade. Furthermore, it presents a comprehensive overview spanning the entire temporal span from 2001 to 2018, enhancing the depth of analytical insights. For Malaysia to maintain global competitiveness, it is imperative to minimize brand switching. Achieving this necessitates the implementation of a robust marketing strategy for pepper products, encompassing assertive publicity efforts and active participation in international trade shows.